The Effect of Squat Training and Leg Length in Increasing the Leg Power of Volleyball Extracurricular Participants - Ahmad Nasrulloh; Putri Deviana; Rina Yuniana; Kukuh Wahyudin Pratama (OVS LLC, 2021)
The study purpose. This study aims to see: (1) The difference in the effect of barbell squat and resistance band squat exercises on the increase in leg power. (2) The difference in influence between players who have high leg height and low leg length on the increase in leg power. (3) The interaction of barbell squat and resistance band squat exercises with leg length (high and low) to increase the power of volleyball extracurricular participants. Materials and Methods. This is an experimental research using a 2 × 2 factorial design. The population in this study were 38 volleyball extracurricular participants at SMA Negeri 1 Sedayu. The sample in this study may be 20 people. Instruments used for measuring: a tape measure for the length of the legs and a vertical jump for the power of the legs. The data analysis technique used was two-way ANOVA. Results. The result showed that (1) There was a significant effect between barbell squat and resistance band squat exercises on the increase in the power of volleyball extracurricular participants, with an F value of 65.789 and a significance value of p = 0.000 (<0.05). The squat group has a higher resistance band (good) compared to the barbell squat group with an average difference of 2.5. (2) There was a significant difference in the effect of players who have high leg height and low leg length on the increase in leg power of volleyball extracurricular participants, it is proven that the F value is 38.000 and the significance value is p = 0.000 (<0.05). Players who have high leg length are higher (good) compared to players who have low leg length with an average difference of 1.90. (3) There was a significant interaction between barbell squat and resistance band squat and leg length (high and low) on the leg power increase of volleyball extracurricular members, with an F value of 88.256 and a significance of p = 0.000 (<0.05). Conclusions. There was a significant difference in the effect of barbell squats and resistance band squats on increasing leg power, there was a significant difference in the effect between players who have high leg length and low leg length on the increase in leg power, and There is a significant interaction between barbell squats and squat resistance bands and leg length (high and low) on the increase in leg power of volleyball extracurricular participants.